2020
DOI: 10.1016/j.isci.2020.101529
|View full text |Cite
|
Sign up to set email alerts
|

First Responders Shape a Prompt and Sharp NF-κB-Mediated Transcriptional Response to TNF-α

Abstract: Summary Nuclear factor (NF)-κB controls the transcriptional response to inflammatory signals by translocating into the nucleus, but we lack a single-cell characterization of the resulting transcription dynamics. Here we show that upon tumor necrosis factor (TNF)-α transcription of NF-κB target genes is heterogeneous in individual cells but results in an average nascent transcription profile that is prompt (i.e., occurs almost immediately) and sharp (i.e., increases and decreases rapidly) compared wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…First, NF-kB dynamics was shown to be qualitatively different between cell lines. The work of Nelson et al (24) already showed how continuous exposure to TNF-a results in oscillations with a time period of 100 minutes in SK-N-AS cells, but less pronounced oscillatory behavior in HeLa cells, as confirmed by others (39,55). Indeed, a study carried out by transducing different cancer cell lines showed how their dynamics upon TNF-a could differ (56).…”
Section: Insights On Nf-κb Response To Stimuli: Heterogeneity With Pr...mentioning
confidence: 83%
“…First, NF-kB dynamics was shown to be qualitatively different between cell lines. The work of Nelson et al (24) already showed how continuous exposure to TNF-a results in oscillations with a time period of 100 minutes in SK-N-AS cells, but less pronounced oscillatory behavior in HeLa cells, as confirmed by others (39,55). Indeed, a study carried out by transducing different cancer cell lines showed how their dynamics upon TNF-a could differ (56).…”
Section: Insights On Nf-κb Response To Stimuli: Heterogeneity With Pr...mentioning
confidence: 83%
“…Our understanding of NF-κB function in the nucleus has increased significantly, but in many cases the cause–effect relationships in the mutual regulation between chromatin regulation and NF-κB-driven events are not very clear. One reason is that most data have been obtained from large cell populations characterized by heterogeneous NF-κB activation patterns [ 95 ]. Comparative analysis of single-cell epigenomic landscapes, NF-κB activation, and transcriptional responses will thus enable determining the precise temporal order of regulatory events and allow establishing causal relations between the diverse regulatory steps [ 96 , 97 , 98 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Immunofluorescence also allows to reveal NF-κB localization to subnuclear regions such as the nucleoli where the p65 subunit accumulates after induction of nucleolar stress [ 85 ] or to cytoplasmic inclusion bodies, as it occurs for example after infection of cells with respiratory syncytial virus [ 86 ]. Additionally, the fusion of NF-κB DNA-binding subunits to fluorescent proteins has been extensively used to study the dynamic oscillations of active NF-κB in living cells [ 43 , 44 , 46 , 87 , 88 , 89 , 90 ]. Further options include combined imaging and flow cytometry instruments (Amnis ® imaging and flow cytometry systems, Luminex, Austin, TX, USA) which facilitate the quantitative analysis of NF-κB nuclear translocation in heterogenous cell populations.…”
Section: Determination Of Nf-κb Activitymentioning
confidence: 99%
“…Single cell assays have revealed that activation of NF-κB and the resulting gene expression patterns can be differentially phased and are highly variable [ 42 , 43 ]. It is possible to find cells with low levels of NF-κB activity adjacent to cells with high activity and strong activation of NF-κB target genes [ 44 , 45 , 46 ]. As many of the latter are secreted proteins, such a behavior may profoundly shape the overall tissue response.…”
Section: Introductionmentioning
confidence: 99%